Evaluation of integrated threshing and drying design concepts for paddy rice using analytical hierarchy process - Opoku-Asante, Johnson; Bobobee, Emmanuel; Akowuah, Joseph O; Asante, Eric Amoah (International Journal of Agricultural Research, Innovation and Technology, 2024)
Threshing and drying are two major postharvest activities that contribute significantly to postharvest losses for small and medium-scale rice farmers, leading to food insecurity and hunger in Sub-Saharan Africa. Developing an appropriate system for threshing and drying needs urgent attention. The objective of the study involved the use of Analytical Hierarchy Process (AHP) for evaluation and selection of the best option among four design concepts for development and fabrication. The four design concepts shortlisted were: (1) batch flow biomass-powered manual threshing and drying system, (2) recirculating diesel-powered mobile threshing and drying system, (3) mechanized threshing with solar drying batch system, and (4) tractor-powered recirculating continues flow integrated system. For the MCAHP analysis, 17 attributes were proposed and divided into five main criteria. The evaluation of the main criteria showed that cost had the highest score, followed by performance, safety, ease of installation and operation, and manufacturability, with a global score of 0.560, 0.202, 0.108, 0.083 and 0.048, respectively. It was observed that design concept two received the highest weighted score of 0.35 and was selected as the design concept to proceed with. The consistency ratios of the main criteria and attributes were all less than 0.1, which is the allowable limit of inconsistency. In conclusion, concept 2 was selected as the best design for developing an integrated threshing and drying system for paddy rice and is recommended for development, fabrication, evaluation and optimisation. Int. J. Agril. Res. Innov. Tech. 14(1): 30-44, June 2024